POTENSI BERPIKIR KREATIF SISWA DALAM PENYELESAIAN SOAL CERITA MATERI SEGITIGA DI SMP - Zuliyanti, Zuliyanti; Sugiatno, Sugiatno; Suratman, Dede (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims is to describe the potention of students in thinking creatively in accomplishing narrative questions about triangle in Senior High School Boedi Oetomo. The method of this study is a case studyÂ by which the resultÂ is explained descriptively. The subject of this researchwas 26 students with the object of the study is creative thinking in accomplishing the questions about triangle. The result of this study shows that the potention of students creative thking in the aspect of fluency scored 80.34 %, 53.84 % for flexibility, 75 % for the originality and 39.42% for the details. It could be concluded that the potention of students creative thinking in acommplishing triangle tasks in form of story questions Boedi Oetomo Senior High School could be categorized as very good in the aspect of fluency, enough for the aspect of flexibility, good in the aspect originality and in the aspect of detail was weak.Key words : Potention of Creative Thinking, Story questions, Triangle Material